Oral microbiome dysbiosis in acute ischemic stroke and transient ischemic attack patients - Duangnapa Roongpiboonsopit; Sirikanya Wairit; Chichaya Nithisathienchai; Akkharin Pakdee; Thanya Cheibchalard; Jarun Sayasathid; Alisa Wilantho; Sissades Tongsima; Naraporn Somboonna (PLoS ONE, 2025)
Oral microbiome (bacterial community) may influence systemic inflammation and vascular health, which both are critical factors in a pathogenesis of ischemic stroke. This study aimed to evaluate differences in the saliva microbiome of acute ischemic stroke (AIS) and transient ischemic attack (TIA) patients compared with matched healthy controls, hypothesizing that AIS and TIA patients are associated with oral microbiome shift. A prospective case-control study was conducted in Naresuan University Hospital, Thailand, to compare the saliva microbiome of AIS and TIA stroke patients of Thai ethnic with matched healthy controls. Microbial profiles were analyzed by metagenomics combined 16S rRNA gene sequencing to assess microbial alpha diversity, taxonomic composition, beta diversity, and microbial functional pathways.Forty-one patients (31 AIS and 10 TIA) and 20 age- and sex-matched stroke-free healthy controls were included in this study. Baseline characteristics were comparable between groups, apart from higher rates of hypertension, diabetes, and smoking in the patient group. Patients exhibited significantly higher alpha-diversity genus richness by OTUs and Chao1 index than controls (p < 0.001), highlighting an altered microbial community structure. Phylum-level analysis revealed an increased abundance of Bacillota (p = 0.0285) in the patient group, with a statistically decreasing trend for Bacteroidota, Actinomycetota and Pseudomonadota (p < 0.05). At the genus level, Streptococcus was more significantly abundant in the patients (p = 0.0171), while Prevotella was reduced. The patient and control groups were statistically separated in beta-diversity analysis (PERMANOVA, p < 0.001), with species biomarker analysis by LEfSe (Linear discriminant analysis effect size) could suggest species markers for each group. Functional pathway analysis showed the patient group the significantly higher in functional categories of, for examples, xenobiotics biodegradation and metabolism, cardiovascular diseases, signal transduction, and membrane transport (Welch’s t-test, p < 0.05). In conclusion, this study demonstrated the statistical alterations in the saliva microbiome of AIS and TIA patients, characterized by increased genus richness diversity and relatively distinct microbial shifts that may be associated with stroke-related inflammation. The findings suggest the saliva microbiome analysis as potential as a non-invasive biomarker for stroke risk and its role in stroke pathophysiology.